The effect of different intensities of magnetically treated water on lipid profile of Turkish- Awassi rams: Suad A. Al-Jashamy1 , Ahmed A. Al-Ani2 and Atheer Salih Mahdi3 - Jashamy, Suad A. (The Iraqi Journal of Veterinary Medicine, 2012)
A total of 15 Turkish- Awassi rams at ages ranged 2 - 2.5 years, and their weight rangedbetween 79.5 – 80.3 kg, Rams were randomly divided into 3 equal groups of 5 rams eachgroup. The first group were taken1000 while the second group were taken 2000 gaussmagnetic water, the third group were taken normal streaming water which is considered as a(control group). Blood sample were taken at the beginning of the experiment, and repeatedevery two weeks during the experimental period (four months). Results revealed that treatedthe rams with magnetically treated water resulted in significantly decreased (p<0.01) incholesterol (1.78-4.08), triglycerides (0.94-0.054), low density lipoprotein (LDL) (1.4-0.2),Very low density lipoprotein (VLDL) (1.87-0.14) and significant increase (p<0.01) in highdensity lipoprotein (HDL)(0.17-0.49) .It could be concluded that rams received magneticallytreated water resulted in significant improvement in level of lipid involved in this experiment.